Global, regional, and national burdens of rheumatoid arthritis among people aged 60 years and older from 1990 to 2021: a trend analysis for the Global Burden of Disease Study 2021 - Su, Qin-Yi; Yang, Liu; Qi, Xiang-Yu; Wang, Meng-Yuan; Cheng, Jing-Wen; Niu, Han; Zhang, Sheng-Xiao (Frontiers in Public Health, 2025)
BackgroundRheumatoid arthritis (RA) poses a significant global health burden, especially among individuals aged 60 and older. This study analyzes RA burden trends using 2021 Global Burden of Disease (GBD) data.MethodsUtilizing the GBD 2021 data, we extracted detailed metric on RA incidence, prevalence, mortality, and disability-adjusted life years (DALYs) specifically for those aged 60 and above. Linear regression analysis was applied to calculate the overall average annual percentage change (AAPC) spanning from 1990 to 2021. Furthermore, Joinpoint regression was employed to identify the years with the most significant changes in global trends. A nuanced stratified analysis was also performed, examining global trends across age groups, genders, and sociodemographic indices (SDI).ResultsFrom 1990 to 2021, both the age-standardized incidence rate (ASIR) and age-standardized prevalence rate (ASPR) of RA in people aged 60 and above worldwide has increased ASIR rose from 24.87 per 100,000 to 30.32 per 100,000 (95% uncertainty interval [UI] 19.83–42.38), while ASPR climbed from 635.51 per 100,000 to 726.91 per 100,000 (95% UI 634.05–834.80). Conversely, the age-standardized death rate (ASDR) and age-standardized DALYs rate declined, with ASDR decreasing from 4.18 per 100,000 to 3.20 per 100,000 (95% UI 2.58–3.72), and DALYs rate dropping from 150.83 per 100,000 to 143.20 per 100,000 (95% UI 113.39–178.43). Regionally, ASIR surged in North Africa and Middle East, Southeast Asia, and Andean Latin America, with ASPR peaking in Andean Latin America. Central Europe saw ASDR decline, while Central Asia’s DALYs rate rose. Nationally, Vietnam’s ASIR soared, and Ireland topped ASIR, ASPR, and DALYs rates. In 2021, for the global population aged 60 and above with RA: ASIR peaked at 65–69 years, ASPR peaked at 75–79 years; ASDR rose with age, and the age-standardized DALYs rate peaked at 85–89 years. Women bore a heavier RA burden. A non-linear SDI-DALYs relationship was noted, with Honduras and Mexico having high DALYs rates.ConclusionFrom 1990 to 2021, the global ASIR and ASPR of RA increased among the older adult, while ASDR and age-standardized DALYs rate declined. Despite improvements, RA remains a public health priority, necessitating enhanced early diagnosis, treatment, and awareness, particularly among older adult women.